2001
DOI: 10.1074/jbc.m104514200
|View full text |Cite
|
Sign up to set email alerts
|

The Docking of Kinesins, KIF5B and KIF5C, to Ran-binding Protein 2 (RanBP2) Is Mediated via a Novel RanBP2 Domain

Abstract: The Ran-binding protein 2 (RanBP2) is a vertebrate mosaic protein composed of four interspersed RanGTPase binding domains (RBDs), a variable and speciesspecific zinc finger cluster domain, leucine-rich, cyclophilin, and cyclophilin-like (CLD) domains. Functional mapping of RanBP2 showed that the domains, zinc finger and CLD, between RBD1 and RBD2, and RBD3 and RBD4, respectively, associate specifically with the nuclear export receptor, CRM1/exportin-1, and components of the 19 S regulatory particle of the 26 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 76 publications
3
129
1
Order By: Relevance
“…Kinesin associates with RanBP2, an important regulator of the nuclear export complex (33). RanBP2 also interacts with CRM1p (exportin1), which binds nuclear proteins via their NES domains and promotes their nuclear export.…”
Section: Figmentioning
confidence: 99%
“…Kinesin associates with RanBP2, an important regulator of the nuclear export complex (33). RanBP2 also interacts with CRM1p (exportin1), which binds nuclear proteins via their NES domains and promotes their nuclear export.…”
Section: Figmentioning
confidence: 99%
“…Specifically, three kinesin-1 genes [kinesin-1A, kinesin-1B, and kinesin-1C, formerly known as KIF5A, -B, and -C (7)] and two KLC genes [KLC1 and KLC2 (24)] have been identified in mammalian nervous tissue. Although the biological significance of this heterogeneity in conventional kinesin subunits is unknown, it might play a role in the selective targeting of conventional kinesin to different cargoes (13) and in the differential regulation of their transport by effector proteins (25). Earlier studies provided partial information on the interaction among selected subunits of conventional kinesin (24,26,27).…”
mentioning
confidence: 99%
“…It was discovered that in retina and brain, the kinesin heavy chain microtubule motors, KIF5B and KIF5C, bind to Nup358 at a specific domain (between Ran binding domains 2 and 3) (Cai et al, 2001). It was suggested that the kinesin plus end directed motor could pay a role in delivering cargo to, or taking it away from, the NPC (Mavlyutov et al 2002), a function that may be more crucial in cells with long distance transport requirements, such as neurons.…”
Section: Nup358 Binds To Kinesinsmentioning
confidence: 99%